2005
DOI: 10.1242/dev.01808
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFIIis essential for radial and anteroposterior patterning of the stomach

Abstract: COUP-TFII, an orphan member of the steroid receptor superfamily,has been implicated in mesenchymal-epithelial interaction during organogenesis. The generation of a lacZ knock-in allele in the COUP-TFII locus in mice allows us to use X-gal staining to follow the expression of COUP-TFII in the developing stomach. We found COUP-TFII is expressed in the mesenchyme and the epithelium of the developing stomach. Conditional ablation of floxed COUP-TFII by Nkx3-2Cre recombinase in the gastric mesenchyme results in dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 25 publications
4
117
0
1
Order By: Relevance
“…In general, COUP-TFI is more highly expressed in the neuronal tissue of the central and peripheral nervous systems, whereas COUP-TFII is expressed in the mesenchyme of developing organs (Pereira et al, 1995). Loss of function assays indicate that COUP-TFI is important for neurogenesis and neural crest cell differentiation during embryonic development Zhou et al, 2001;Yamaguchi et al, 2004), while COUP-TFII acts as a major regulator of angiogenesis, vein identity, and organ development (Pereira et al, 1999;Takamoto et al, 2005;You et al, 2005). In the cerebellum, the expressions patterns of these two receptors are not co-localized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, COUP-TFI is more highly expressed in the neuronal tissue of the central and peripheral nervous systems, whereas COUP-TFII is expressed in the mesenchyme of developing organs (Pereira et al, 1995). Loss of function assays indicate that COUP-TFI is important for neurogenesis and neural crest cell differentiation during embryonic development Zhou et al, 2001;Yamaguchi et al, 2004), while COUP-TFII acts as a major regulator of angiogenesis, vein identity, and organ development (Pereira et al, 1999;Takamoto et al, 2005;You et al, 2005). In the cerebellum, the expressions patterns of these two receptors are not co-localized.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike COUP-TFI, COUP-TFII is highly expressed only in the anterior half of the cerebellum in a manner similar to that of Sonic hedgehog (Shh), which is important for cerebellar foliation (Corrales et al, 2004(Corrales et al, , 2006. Since COUP-TFII is more likely to be a downstream target of Shh signaling (Krishnan et al, 1997;Takamoto et al, 2005), it is reasonable to expect that COUP-TFII may play an important role in cerebellar development. Additionally, when one considers the temporal expression pattern of COUP-TFI and ERR␄, it is probable that they may also function during cerebellar development.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for generating Prox1 Ï©/LacZ , COUP-TFII flox/flox , and Prox1 Ï©/GFPCre mice were previoulsy reported. 4,10,11 PlexinD1 ÏȘ/ÏȘ embryos were previously described. 12 All of the mouse experiments were approved by the St Jude Children's Research Hospital Animal Care and Use Committee.…”
mentioning
confidence: 99%
“…COUP-TFII-deficient mice die in utero with defects in heart development and angiogenesis. Tissue-specific knock-out studies have shown that COUP-TFII is required for the development of limb, skeletal muscles, and stomach and plays a critical role in determining vein identity (11,13,14). Even though the ligands of COUP-TFII are still unknown, the roles of COUP-TFII during angiogenesis, female reproduction, and neurogenesis have been well established.…”
mentioning
confidence: 99%